New Religious Movements in a Secular State - LAVRRENTIEVA, Maria Sergeyevna; TURKIN, Mikhail Mikhailovich; KUCHENIN, Evgeny Sergeevich; VOLKOVA, Maria Alexandrovna; ZOLOTAREVA, Alla Efratovna (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).14, 2020)
The research analyzes problems associated with new religious movements in a secular state, using the example of the Russian Federation. It has been established that a state in which religion and the state are separated from each other is recognized as secular. The state and state bodies are separated from the Church and religious associations and do not interfere with their activities. In turn, the latter do not interfere with the activities of the state and state bodies. A secular state implies: the absence of any religious authority over state bodies, the inadmissibility of the performance of any state functions by the Church or its hierarchs; the absence of compulsory religion for public servants and authorities; the state's non-recognition of the legal significance of Church acts and religious rules as sources of law; the state's refusal to finance the expenses of any Church or religious organization. The purpose of this article is to review, define, and comprehensively analyze the legal regulation of new religious movements in Russia, as well as to determine the legal status of these organizations, their activities and relationships with the state and state bodies.